2022
DOI: 10.3389/fvets.2022.924736
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and antimicrobial susceptibility pattern of Escherichia coli O157:H7 from foods of bovine origin in Mekelle, Tigray, Ethiopia

Abstract: Escherichia coli O157:H7 is an emerging and major zoonotic foodborne pathogen. It has an increasing concern about the spread of antimicrobial-resistant strains. This study aimed to isolate and characterize Shiga toxin-producing E. coli O157:H7 from raw milk, yogurt, and meat of bovine origin and determine their antimicrobial susceptibility pattern. A cross-sectional study was conducted from December 2014 to June 2015, and a total of 284 milk and meat samples were collected from different sources in Mekelle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…are frequently detected in yogurt, are sometimes present in concentrations above the normative levels, and consequently may have adverse effects on consumer health[6,7].The result of tetracycline resistance was more frequently observed compared with the other antibiotics of E. coli isolates in this study, in agreement with the reports of Tadesse et al,. 2021 [28] (27.7%) and lower than the ndings of Gugsa et al,2022[9] (41.7%),Messele et al,2017 [29] (47.6%), Ahmed and Shimamoto,2015[30] (80.6%),Disassa et al,2017 [31] (81.8%),Ababu et al,2020 [32] (63.63%), and Hailu,2020[33] (60.61%) but was higher than the ndings ofBekele et al,2014…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…are frequently detected in yogurt, are sometimes present in concentrations above the normative levels, and consequently may have adverse effects on consumer health[6,7].The result of tetracycline resistance was more frequently observed compared with the other antibiotics of E. coli isolates in this study, in agreement with the reports of Tadesse et al,. 2021 [28] (27.7%) and lower than the ndings of Gugsa et al,2022[9] (41.7%),Messele et al,2017 [29] (47.6%), Ahmed and Shimamoto,2015[30] (80.6%),Disassa et al,2017 [31] (81.8%),Ababu et al,2020 [32] (63.63%), and Hailu,2020[33] (60.61%) but was higher than the ndings ofBekele et al,2014…”
mentioning
confidence: 75%
“…Studies and observations conducted elsewhere in Ethiopia have also indicated that the increase in the proportion of antimicrobial-resistant strains could be due to the irrational use of antimicrobials and the inappropriateness of the prescription and dispensing methods in both the public veterinary and private health setups of the country [12,43]. The scienti c literature indicates that the presence of multidrugresistant bacterial pathogens in ruminants, and consequently in dairy products, may cause drug-resistant infections in humans [14,15,8,9,10,11,12,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations